UV Photodetector based on Al-doped ZnO Nanocrystalline Sol-gel Derived Thin Fims - K. Chongsri; W. Pecharapa (My University, 2014)
Aluminum doped zinc oxide (AZO) thin films were studied as an UV photodetector devices. The AZO thin films were prepared on FTO substrates by spin coating technique. All samples exhibit prominent optical absorption edge with high optical transparency in visible range and significant blue-shift in optical band gap with increasing Al composition. The photoilluminated current increases linearly with increasing bias voltage reflecting ohmic contact behavior. The detectors have excellent ultraviolet response in wavelength region of 250-380 nm suggesting that tunable wavelength response can be obtained by increasing Al composition.
Keywords: Ohmic contact; Nanocrystalline material; Absorption edge; Spin Coating; Ultraviolet; Biasing; ZnO doping and properties